Curating the Everywhere Museum of Everything. Issue 3 (2nd July 2020) - Alves da Veiga, Pedro
ABSTRACT: The Everywhere Museum of Everything is a research and action proposal founded on the array of aestheticised online content, which can be purposefully and critically curated in order to create a meaningful territory of contemporary online culture, art and knowledge creation. This abundance of content is rooted in a culture of consumerism, blackboxed mobile applications and social networks. Individual experiences in the physical world have been transformed by onlineness, a combination of the pervasive use of mobile devices and applications over Internet access, used to share opinions and evidence through original and remixed media, often complemented by hashtagging . Even if the majority of this content quickly becomes irrelevant and forgotten, it can still be accessed through an augmented view of the world, as digital media is frequently anchored to locations through geo-tagging or referencing. This vast collection lacks systematization and classification, but presents multiple possibilities for artists, curators and scholars.